Serologic Evidence of Frequent Human Infection with WU and KI Polyomaviruses - Nguyen, Nang L. (Centers for Disease Control and Prevention, 2009)
WU polyomavirus (WUPyV) and KI polyomavirus (KIPyV) are novel human polyomaviruses. They were originally identified in human respiratory secretions, but the extent of human infection caused by these viruses has not been described to date. To determine the seroepidemiology of WUPyV and KIpyIV, we used an ELISA to screen serum samples from 419 patients at the St. Louis Children’s Hospital and Barnes-Jewish Hospital during 2007–2008. The age-stratified deidentified samples were examined for antibodies to the major capsid proteins of WUPyV and KIPyV. Seropositivity for each virus was similar; antibody levels were high in the youngest age group (<6 months), decreased to a nadir in the next age group (6 to <12 months), and then steadily increased with subsequent age groups, eventually reaching a plateau of ≈80% for WUPyV and ≈70% for KIPyV. These results demonstrate that both KIPyV and WUPyV cause widespread infection in the human population.